The rad16 gene of Schizosaccharomyces pombe: a homolog of the RAD1 gene of Saccharomyces cerevisiae. - Carr, A M (1994)
The rad10, rad16, rad20, and swi9 mutants of the fission yeast Schizosaccharomyces pombe, isolated by their radiation sensitivity or abnormal mating-type switching, have been shown previously to be allelic. We have cloned DNA correcting the UV sensitivity or mating-type switching phenotype of these mutants and shown that the correcting DNA is encompassed in a single open reading frame. The gene, which we will refer to as rad16, is approximately 3 kb in length, contains seven introns, and encodes a protein of 892 amino acids. It is not essential for viability of S. pombe. The predicted protein is the homolog of the Saccharomyces cerevisiae RAD1 protein, which is involved in an early step in excision-repair of UV damage from DNA. The approximately 30% sequence identity between the predicted proteins from the two yeasts is distributed throughout the protein. Two-hybrid experiments indicate a strong protein-protein interaction between the products of the rad16 and swi10 genes of S. pombe, which mirrors that reported for RAD1 and RAD10 in S. cerevisiae. We have identified the mutations in the four alleles of rad16. They mapped to the N-terminal (rad10), central (rad20), and C-terminal (rad16 and swi9) regions. The rad10 and rad20 mutations are in the splice donor sequences of introns 2 and 4, respectively. The plasmid correcting the UV sensitivity of the rad20 mutation was missing the sequence corresponding to the 335 N-terminal amino acids of the predicted protein. Neither smaller nor larger truncations were, however, able to correct its UV sensitivity.